Analisis Ketersediaan Tenaga Perawat di Instalasi Rawat Jalan Rumah Sakit Restu Ibu Balikpapan - Larasati, Larasati; Qohardita, Risa; Arumjati, Vernillina Oktaeighta; Purwadhi, Purwadhi; Widjaja, Yani Restiani (Universitas Pahlawan Tuanku Tambusai, 2025)
Nurses are medical personnel who take many important roles in patient care. Not only how to monitor the patient's condition as a whole, ensuring that patients receive services according to standards, nurses also coordinate with other medical personnel, even non-medical units to ensure that patients also carry out their obligations as patients. Seeing that the role of nurses is very large, an adequate number of nursing staff is one of the basics of quality service. Nurses are the spearhead of hospital health services, so the availability of nurses in quantity and quality is an important part in planning the Human Resources unit. RS. Restu Ibu is in the process of transitioning the nursing staff from the Outpatient Installation, most of which are part-time to full time, so it requires an analysis and calculation of the number of nursing staff needed according to the conditions of this unit. This study aims to analyze the availability of nurses in outpatient installations by measuring workload. Workload measurement is carried out through subjective and objective approaches. Subjective measurements use workload questionnaires, while objective measurements use the WISN method. The sample size consisted of 20 people. Data collection methods involve interviews, observation, and document study. Descriptive analysis was applied to interpret the results of both measurement methods. The results of subjective workload measurements show that the nurses' workload is in the medium category, while objective workload measurements require the addition of 3 nursing staff. With the results of this analysis, it is hoped that it can increase the productivity of nurses' performance which will support the quality of hospital services.